Singular Value Decomposition Method: Application to Design of Observer-Based Control for Uncertain Atangana-Baleanu-Caputo Fractional-Order One-Sided Lipschitz Nonlinear Systems - Hong, Duong Thi (Discontinuity, Nonlinearity, and Complexity, 2026)
In this paper, the problems of observer-based control design and asymptotically stable for uncertain Atangana-Baleanu-Caputo fractional-order one-sided Lipschitz nonlinear systems have been considered. The purpose of this problem is that we design observer-based controller to ensure that the controlled system is asymtotically stable by using singular value decomposition method (SVD) and a well-behaved property of the Atangana-Baleanu-Caputo fractional calculus. The results are obtained in terms of LMI, which can be effectively solved in polynomial time by various computational tools. Finally, a numerical example has been presented to show the simplicity of our design method.